The relationship between mutual fund flows and market variables / Fiza Qureshi - Fiza , Qureshi (2017)
The mutual fund industry has become an important investment choice, especially in high and middle-income countries, because of the investment considerations, such as safety, information, liquidity and diversification. The existing literature, however, has been more focused towards mutual funds’ performance at the micro level in advanced economies. On the other hand, the literature on the macro aspects of mutual funds in developing economies is scarce and inconclusive. This study investigates the empirical relationship between aggregate mutual fund flows, stock market variables and macroeconomic variables for developing countries from the Association of South East Asian Nations (ASEAN), the Middle East and North African region (MENA), Brazil, Russia, India, China and South Africa (BRICS), and the South Asian Association for Regional Cooperation (SAARC). The three popular theories in flow-market-economy relationship are examined using four mutual fund flows classes, two stock market variables, and selected macroeconomic variables. Moreover, the study also examines the ability of mutual funds to predict macroeconomic conditions. For the flow-returns relationship, there is bidirectional causality between all fund flow classes (except for the bond fund flow) and stock market returns. Stock returns move parallel to equity and balanced fund flows, and contrary to money market flows. For bond fund flows, the causality runs from the stock market to bond fund flows such that the increase in lagged returns decreases the growth of bond fund flows. For the flow-volatility relationship, there is a bidirectional causality between all classes of mutual funds (except for the bond funds) and stock market volatility. Market volatility increases with increase in money market funds and decreases with increase in equity and balanced flows. Furthermore, the fund flows are linked with both the current and the lagged volatility. The mutual funds respond concurrently to the risk-related information as compared to the return-related information in the stock market. In addition, risky securities have a stronger relationship with market variables than the less risky securities do. With respect to the flow-market returns-economy relationship, causality runs from market returns to mutual fund flows such that mutual fund flows react positively to the past performance of the market. In case of flow-market volatility-economy relationship, the bidirectional causality exists even after incorporating macroeconomic variables. The findings also suggest that macroeconomic variables influence fund flows, market returns and market volatility. Macroeconomic variables that possess good (bad) news are positively (negatively) associated with the fund flows and market returns (market volatility). Fund flows are forward-looking and assist in forecasting real economic conditions. Furthermore, the risky funds invest more in times of good economic conditions, while the less risky funds invest more in times of poor economic conditions: for instance, good (bad) macroeconomic news is positively (negatively) associated with the risky fund flows (less risky fund flows). The research inference is that investors in these markets direct flows away from the equity-based funds to the fixed income-type funds in times of high market and macroeconomic risk.